Challenging Electoral Integrity: The Constitutionality of the 'Empty Box' Victory in the 2018 Makassar Mayoral Election - Muhammad Akbar; Maisa Maisa (Lex Scientia Law Review, 2024)
Single-candidate regional elections have recently attracted significant attention, as previous regulations did not adequately address scenarios where fewer than two candidate pairs were running. The 2018 Makassar mayoral election, where the "Empty Box" (Kotak Kosong) emerged victorious against a single candidate, highlights a critical constitutional issue: whether such an outcome is consistent with the principles of democratic electoral integrity. In elections featuring only one candidate pair, the ballot contains two columns—one with the candidate's photo and name, and the other left blank. The constitutionality of allowing the "Empty Box" to win in such circumstances poses significant questions about the fairness of the electoral process and the safeguarding of citizens' constitutional rights. This research critically examines the legal implications of this electoral anomaly and explores the necessity for clear legislative frameworks governing single-candidate elections. The case offers important lessons for Indonesia’s political and electoral systems, emphasizing the need for constitutional and electoral reforms to protect citizens' rights—both the right to vote and the right to be elected—even when only one candidate is on the ballot. Furthermore, it underscores the urgency of political education for both political parties and the electorate to foster a more informed political culture. By analyzing the legal precedents, constitutional principles, and broader implications, this study contributes to the discourse on electoral reform, ensuring that Indonesia’s electoral system remains robust, fair, and reflective of democratic values.